Evaluation of Glycemic and Hepatic Markers in Patients with Non-Alcoholic Fatty Liver Disease (NAFLD) Treated with Pioglitazone - Asia Firdous, Ghulam Ovais Qarni, Javeria Sarfraz, Muzamil Liaqat Ali, Arooj Fatima, Waleed Arshad (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Non-Alcoholic Fatty Liver Disease (NAFLD) is a prevalent metabolic disorder characterized byhepatic steatosis in the absence of significant alcohol consumption. Recent therapeutic strategieshave explored the efficacy of pioglitazone